Microarrays—Solutions to the Protein Challenge. (January 2005) - Clarke, Jeremy
The study of the proteome presents many challenges to the researcher. One of these is finding the best way to study tens of thousands of proteins in as short a time as possible. With the advances in miniaturization and automation over the recent past, several approaches are now available for producing high-density protein arrays on custom slides. After the arraying process is complete, lessons learned in the automated hybridization and imaging of cDNA and oligonucleotides now allow the consistent high-throughput study of antibody/antigen interactions.